OYSTER MUSHROOM CULTIVATION AS ISLAMIC EDUCATIONAL TOURISM OF BANJARDOWO VILLAGE SEMARANG CITY - Mochamad Ainan; Pranoto; Mengku Marhendi (Universitas Mathla’ul Anwar Banten, 2022)
Banjardowo Tourism Village is characterized by oyster mushrooms / thematic villages which are known by the community as Banjardowo Tourism Villages which have the potential to be able to plant and manage oyster mushrooms successfully and provide education to people about how to cultivate oyster mushrooms. Research in Banjardowo Village, Genuk District, Semarang City. The data processing technique used is descriptive qualitative. The data will be presented in the form of a qualitative narrative expressed in verbal form which is processed to be clear, accurate and systematic. The method used is a survey method with a qualitative approach, Oyster mushroom production is still low because consumer demand is quite high. Community empowerment in the cultivation and processing of oyster mushroom products is very necessary considering the prospect of oyster mushroom cultivation is very promising if the quality and quantity of the product is in accordance with the requirements. Utilization of the potential for educational tourism in Banjardowo Village has been initiated by packaging the process of oyster mushroom cultivation and processing of oyster mushroom harvests while still paying attention to the cultural elements of the community based on Islamic values.